Panorama das condições de trabalho na monocultura do milho dos produtores assentados do município de Simão Dias, Sergipe - Souza, Juliana Gois de (2022)
In Brazil, according to the 2017 Agro Census (IBGE, 2017), family farming represents a contingent equivalent to 77% of agricultural establishments in the country. In the state of Sergipe, according to the IBGE, this form of production is also equivalent to 77% of the 93,000 rural establishments in the state, where the main crops are corn, cassava, rice, beans, bananas, oranges and sugar cane. (IBGE, 2019), with corn having great relevance in the state economic scenario, whose 2020/2021 harvest was equivalent to 687.6 thousand tons, with 820,178 ha of cultivated area, and average productivity of 3,685 kg/ha (CONAB, 2022). ). Among the municipalities that produce this crop, it is noteworthy that Simão Dias is considered the second largest corn producer in the state, with a predominance of this type of monoculture in the 8 de Outubro and 27 de Outubro settlements, with a considerable technological level in agricultural production systems. and strong presence of family farming. Despite the representativeness of corn cultivation in family farming establishments, it is not possible to identify the existence of specific rules aimed at regulating the activity of workers who work directly in these crops, despite the techniques that are used, such as the widespread use of pesticides. , machinery, etc. In this way, the present study aims to analyze the aspects of working conditions and the possible consequences arising from the cultivation of corn, on the health of family farmers who develop their activities in the Settlements 8 de Outubro and 27 de Outubro, in the municipality of Simão Dias - SE , observing the applicable legislation. The study carried out is descriptive and analytical, whose approach is based on mixed methods, using qualitative and quantitative techniques, through bibliographic and field research, the latter with the application of semistructured questionnaires to settled family farmers and key informants, according to the "Snow ball" methodological tecnique. With the study carried out,it was found that Brazilian legislation is broad in terms of occupational risks and safety mechanisms, but still not very applicable to the scenario of family farming workers; the methods used in corn cultivation pose risks to the health of family farmers; technical assistance in the studied regions does not exist or is shown to be deficient; and the performance of the Public Power is shown to be inefficient, which makes it impossible to regularly implement the appropriate mechanisms for the healthy performance of the work activities of these social actors.